Experimental Study on the Structural Performance Degradation of Corrosion-Damaged Reinforced Concrete Beams - Ju-Seong Jung; Bang Yeon Lee; Kang-Seok Lee (Advances in Civil Engineering)
It is very important to investigate the effects of the seismic performance of corrosion-damaged reinforced concrete (RC) members, in terms of their strength and lateral deformability, on the seismic performance of entire building systems. Such investigation allows accurate evaluation of the seismic performance of RC structures with corroded members, including beams and columns. However, current techniques for evaluating the seismic performance of existing RC structures do not take the effects of deterioration (including the corrosion of reinforcing bars) on the performance of RC members into account. The main objective of this research is to propose a practical methodology for evaluating the seismic performance of RC buildings with corrosion-damaged members. We extrapolate a structural performance degradation factor from the strength-deformation capability of corroded members to allow direct quantitative evaluation of their seismic performance. In this study, as a first step toward achieving this goal, we experimentally investigated the effect of reinforcing bar corrosion on the behavior of RC beams and the structural performance degradation factor. Our analysis was based on the strength-deformation capabilities of corrosion-damaged beams. We also propose a relationship between the half-cell potential of corroded reinforcing bars and the structural performance degradation behavior of RC beams. Our results indicate that there is a relatively strong correlation between the performance degradation factor and the average potential difference, with coefficients of determination (R2) of the flexural and shear beams of 0.78 and 0.91, respectively. The potential difference, which was measured using the half-cell measurement method, can serve as one of the indicators of relative structural degradation, but we must ensure that the environmental measurement conditions are held constant.